As novas dinâmicas das rotinas produtivas nas revistas Trip e TPM e o uso das redes sociais na internet - Guimarães, Rackel Cardoso Santos (2015)
Convergence is a process that causes changes in journalism, not only with the introduction of new electronic equipment, but also in the physical context of the writing and the productive routines. The technological age in which we live, marked by the speed and interactivity, changed the ways of producing and disseminating news, as well as in the forms of and consume and share them. The internet has attracted more and more followers and expanded around the world. Through it an avalanche of information comes to social actors that seek besides, and entertainment, a daily source of information on the news portals, aggregate sites of news organizations and even on the social networks. The integration of social networks in daily life and newspaper companies, caused behavioral changes and ended up turning the public, from viewer to co-producer, and creating new channels of reverb news, through the interaction of actors with newspaper companies and other actors. In this context the spread of social networking profiles such as Facebook, Twitter and Instagram, used as new platforms for dissemination and interaction, changed the magazine journalist everyday. Print publications have also been inserted in this context of convergence, which has created new forms of production and dissemination of content once only printed. In this scenario, the main objective of this dissertation is to analyze what were the changes caused by journalistic convergence, specifically, with the inclusion of social networks in day-to-day of the Trip and TPM magazines redaction, whose teams work seamlessly to both magazines in the media printed, digital and online. This is a study through literature review, data collection published on social networking profiles of magazines, productive routine analysis through the ethnographic method of participant observation and interviews. What enabled us to know and analyze this new production in which the magazines are inserted. During a search encounter hum process adaptations and changes Trip and TPM Magazines . use of social networks is part of them, where the public interacts directly with the journalist And work has a more fast, but the content published on these networks work , most of the time , only how marketing strategy . The internet has made magazines as were presented to hum new audience, so the number of followers of the social networking profiles he spent be greater than make a circulation of printed magazines. In addition, an essay integrated and platform working conditions created new labour and new challenges professionals.